Smart clothing for control and health monitoring - Turdaliyev Khusan Inomjonovich; Maqsudov Nabijon Bahadirovich; Usanova Gulshoda Ibroximjon kizi; Yusupov Dilshodbek Solijon oglu (Global Scientific Publishing, 2025)
This scientific article discusses the technology for producing smart clothing for people with heart problems. The project integrates health monitoring with analytics, security, and timely medical alert systems. Smart clothing, developed based on sensor modules, biometric monitoring, GPS, and real-time cardiogram technologies, is proposed as an innovative solution for detecting and preventing heart-related risks
Keywords: Heart defect; smart clothing; biometric monitoring